Diseño termo-hidráulico de una caldera para la recuperación de energía de los gases de escape de una turbina a gas - Mena, Fabrizzio (2011)
The main objective of this graduation project was to determine the strength and viability of the boiler, through the design of a mathematical model that could perform the necessary calculations for the analysis of this system and know the characteristics of both the heat source as the p and temperature, and using the results to determine whether the design of this boiler is correct. This heat recovery system, formed by superheated steam or heat flux from the combustion gases from gas turbine. The design starts by knowing the heat flow rates over which it will work the gas turbine, for the project takes th range of a gas turbine model LM 5000, then performed the analysis of heat exchanger through the use of logarithmic mean temperature and cross flow, which is set flows which were present in the boiler heat. The analysis is carried out through the heat tra and the economizer, to gain the ability to transfer heat to the water, which is within the tubes